An evaluationof the mathematics program for the gifted/talented at the International School, Manila - Lim, Vivian V. (Education quarterly.)
The mathematics program for the academically gifted/talented program in the grades 3, 4, and 5 at the International School, Manila (I.S.M.) is evaluated in this study. This evaluation involves an assessment of both the process and the product dimensions of the program.